Driving Indonesian public sector innovation with strength-based leadership: The role of psychological safety and ambidextrous organizational culture - Osi Isna Sabela; Arum Etikariena (Jurnal Psikologi Tabularasa, 2025)
Innovation is essential for achieving organizational excellence. Civil servants need to embrace this demand, as reflected in the core values of Ber-AKHLAK. This underscores the urgent need to investigate the factors that drive innovative work behavior (IWB) in the public sector. This study highlights strength-based leadership (SBL) as a key factor influencing IWB. Using Social Exchange Theory, the research investigates the mediating role of psychological safety (PS) and the moderating effect of an ambidextrous organizational culture (AOC). A quantitative self-report survey was distributed via social media, collecting responses from 354 civil servants in Indonesia. The adapted measurement scale demonstrated reliability. Analysis with PROCESS Macro Model 14 in SPSS version 29 indicated that SBL significantly generated IWB directly and through PS, but AOC did not significantly moderate this relationship. These findings imply that although civil servants positively perceive the ambidextrous culture in their organization, it does not automatically boost innovative behavior. Leadership focusing on workers' strengths is more meaningful for activating the psychological safety necessary for innovation.